THE EFFECT OF CAR, NPL AND LDR ON THE PROFITABILITY OF REGIONAL DEVELOPMENT BANKS IN JAVA FOR THE PERIOD 2019-2023 - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2024)
Due to the dependency of the younger generation on digital solutions, the banking sector in Indonesia is going through a period of fierce rivalry, both in terms of goods and services and technological innovation. The products, services, and technological infrastructure that banks offer to their customers are designed to make financial transactions and activities more accessible and more convenient. One of the most important indicators of a bank's success and prospects is profitability, which can be quantified using a ratio, such as Return on Assets (ROA). This is because profitability involves a diverse variety of stakeholders. This study aims to investigate the influence of CAR, NPL, and LDR ratios on the profitability (ROA) of the Regional Development Bank in Java, both partially and simultaneously. ROA is the dependent variable in this study, while CAR, NPL, and LDR are the independent variables. The analysis tools utilized in this study were SPPS Version 26, and the methodology included basic and multiple regression tests. This study found that between 2019 and 2023, the CAR, NPL, and LDR factors partially and simultaneously impacted the profitability (ROA) of the Regional Development Bank in Java.